Improving the financial condition of the company - Yuri Ivanov (Cхід, 2013)
In this paper, based on the study of publications found that the operation of the financial state of Ukrainian enterprises at the current time can be characterized as based on the principles of open government. Almost control actions at the enterprise does not control the final results. At best we can talk about the elements of the principle of management by exception, but with so much lag control actions, which eliminates the possibility of operational management.